Male Plants of Cyrtomnium hymenophylloides (Bryophyta: Mniaceae) in Siberia - N. G. Miller; Mogensen, G. S. (Arctoa, 2000)
Male plants of the arctic-alpine moss Cyrtomnium hymenophylloides are present in a collection of this species from the unglaciated Lena River Valley, Siberia, Asian Russia. Male plants are otherwise known from near or in unglaciated refugia in arctic Canada and Alaska. Female plants are more widespread in northern regions of glaciated North America and Fennoscandia. The differential distribution of male and female plants, and the apparent absence of sporophytes in the few known places were males and females occur together, indicate that there is limited potential of dispersal by spores throughout the range of this moss, and not only in North America as was previously documented.
Keywords: arctic-alpine; Asian Russia; Cyrtomnium hymenophylloides; Lena River Valley; moss; Siberia